The Fundamentalist Voter: Politicized Religious Identity and Political Attitudes and Behavior - Wilcox, Clyde (Review of religious research, 1989)
We now know that evangelical Christians are not an homogeneous group, but differ on religious and political grounds. This paper explores one of the main fault lines in the evangelical community: the difference between fundamentalists and other evangelicals. Using the framework of politicized group identification, I argue that a fundamentalist self-identification has no political meaning for those who are not exposed to messages from religious-political elites seeking to develop a politicized group consciousness. Among those exposed to these messages, however, fundamentalists are more conservative and more Republican than other evangelicals.